Invitro Evaluation Of The Effect Of Fetal Hemoglobin Inducer Drugs On Proliferation And Differentiation Of Erythroid Progenitors With β -Thalassemia Gene Mutation - Zahra Kashani Khatib; Ali Dehghanifard; Saeid Kaviani; Mehrdad Noruzinia; Momeneh Mohammadi; Fatemeh Mohammad Ali; Elham Roshandel; Sahar Mohammadi Fateh; Shaban Alizadeh (Tehran University of Medical Sciences, 2014)
Background and Aim: Understanding the molecular mechanisms involved in the increased levels of HbF inducing drugs should be advised for effective induction. The aim of this study was to investigate the molecular effects of the drugs thalidomide and sodium butyrate considered as HbF inducer agents.  Materials and Methods: In this experimental study, CD133+ cord blood stem cells carrying mutations of heterozygous β-thalassemia were isolated and differentiated into erythroid lineage. In order to evaluate the expression of the erythroid markers, CD71 and CD235a, was analysed. For this purpose, the RNA extracted from erythroid precursors at days 6 and 12 of erythroid differentiation and cDNA synthesized, and then the expression of these genes was performed by quantitative Real-time PCR technique.  Results: The results of this study showed the significant effect of thalidomide on erythroid proliferation as compared to sodium butyrate and control group (P<0.05). Also, thalidomide significantly increased CD71expression and decreased CD235a expression as compared to sodium butyrate and control groups (P<0.05).  Conclusion : Thalidomide may play its role on HbF induction by increasing the proliferation of early erythroid precursors.